Lost in the city : a Julie mystery - O'Dell, Kathleen, 1957- (American Girl mysteries., 2013)
In 1970's San Francisco, Julie is excited to take care of Ivy's talking parrot while her friend is on vacation, but strange things are happening at Ivy's house and an old friend of Julie may be to blame.